Implementasi Manajemen Perubahan “Pada Mie Uda Bro Padang” - Fatia Rahmi Nelsya; Afrina Helka Putri; Danil Elfira; Rosanti; Ramdani Bayu Putra (STIKes Ibnu Sina Ajibarang, 2024)
Change management is a very crucial aspect in maintaining the survival and growth of Mie Uda Bro Padang. Changes here can include changes in technology, market competition, regulatory policies, and consumer tastes. In this context, change management refers to the process of planning, implementing and monitoring changes that will help Mie Uda Bro Padang to remain relevant and competitive. In this context, effective change management will be the key to the success of Mie Uda Bro Padang. Efforts to identify needed changes, plan these changes, communicate changes to the entire team, provide necessary training, and monitor the results of changes are essential to ensure the success of these MSMEs.